The Camp Nou Stadium as a Testbed for City Physiology: A Modular Framework for Urban Digital Twins. (12th October 2021) - Meta, Irene; Serra-Burriel, Feliu; Carrasco-Jiménez, José C.; Cucchietti, Fernando M.; Diví-Cuesta, Carla; García Calatrava, Carlos; García, David; Graells-Garrido, Eduardo; Navarro, Germán; Làzaro, Quim; Reyes, Patricio; Navarro-Mateu, Diego; et al.
Abstract : In this paper, the Camp Nou stadium is used as a testbed for City Physiology, a theoretical framework for urban digital twins. With this case study, the modularity and adaptability of the framework, originally intended for city-scale simulations, are tested on a large facility venue. As a proof of concept, several statistical techniques and an agent-based simulation platform are coupled to simulate a crowd in the stadium, and a process of four steps is followed to build the case study. Both the conceptual (interdomain) and technical (domain specific) layers of the digital twin are defined and connected in a nonlinear process so that they represent the complexity of the object to be simulated. The result obtained is a strategy to build a digital twin from the domain point of view, paving the way for more complex, more ambitious simulators.